2014
DOI: 10.3390/coatings4030465
|View full text |Cite
|
Sign up to set email alerts
|

A Study of a Powder Coating Gun Near Field: Particle Flow in an Isothermal Staggered Concentric Air Jet

Abstract: An experimental study of inert particle dispersion in an isothermal concentric air jet near field was conducted for cases of standard non-staggered and alternative staggered jet nozzles, each taken from a polymer powder flame deposition gun. The experimental work consisted of analysis of high speed digital images of the inert two phase isothermal jet flow, illuminated by a laser light sheet along and across the jet axis. The analysis of particle spread in the jet, represented by families of particle density di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 18 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…The flow visualization used a sheet of laser light, created by the apparatus shown in Payne et al, placed either through the centreline of the gun head to illuminate each jet from its origin, or at a right angle to the axis of the coaxial air jet just downstream of the origin of the central jet. When the sheet of laser light was placed longitudinally, it was positioned so that it illuminated four nozzles emitting air or CO 2 (in place of propane), two on one side of the coaxial air jet, one each from the inner and outer rings, and the two diametrically opposite them.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The flow visualization used a sheet of laser light, created by the apparatus shown in Payne et al, placed either through the centreline of the gun head to illuminate each jet from its origin, or at a right angle to the axis of the coaxial air jet just downstream of the origin of the central jet. When the sheet of laser light was placed longitudinally, it was positioned so that it illuminated four nozzles emitting air or CO 2 (in place of propane), two on one side of the coaxial air jet, one each from the inner and outer rings, and the two diametrically opposite them.…”
Section: Resultsmentioning
confidence: 99%
“…Two earlier papers by Payne et al reported on experimental and numerical studies of the flow field created by an innovative gun head design for a polymer flame deposition process. Payne et al studied the isothermal air‐only coaxial jet.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations